Variable impact of tizanidine on the medium latency reflex of upper and lower limbs - Kurtzer, Isaac; Bouyer, Laurent J.; Bouffard, J.; Jin, A.; Christiansen, L.; Nielsen, J. B.; Scott, S. H. (Experimental brain research, 2018)
Sudden limb displacement evokes a complex sequence of compensatory muscle activity. Following the short-latency reflex and preceding voluntary reactions is an epoch termed the medium-latency reflex (MLR) that could reflect spinal processing of group II muscle afferents. One way to test this possibility is oral ingestion of tizanidine, an alpha-2 adrenergic agonist that inhibits the interneurons transmitting group II signals onto spinal motor neurons. We examined whether group II afferents contribute to MLR activity throughout the major muscles that span the elbow and shoulder. MLRs of ankle muscles were also tested during walking on the same day, in the same participants as well as during sitting in a different group of subjects. In contrast to previous reports, the ingestion of tizanidine had minimal impact on MLRs of arm or leg muscles during motor actions. A significant decrease in magnitude was observed for 2/16 contrasts in arm muscles and 0/4 contrasts in leg muscles. This discrepancy with previous studies could indicate that tizanidine’s efficacy is altered by subtle changes in protocol or that group II afferents do not substantially contribute to MLRs.